PENANAMAN NILAI-NILAI TOLERANSI ANTAR UMAT BERAGAMA PADA SISWA SMPN 1 KAPUAS TENGAH - Norjannah, Norjannah; Qomariyah, Nurul (ADDABANA: Jurnal Pendidikan Agama Islam, 2024)
Abstract: This research discusses the instilling of inter-religious tolerance values in students at SMPN 1 Kapuas Tengah. The formulation of the problem in this research is the Instillation of Religious Tolerance Values at SMPN 1 Kapuas Tengah, the obstacles faced in instilling the values of religious tolerance at SMPN 1 Kapuas Tengah. The subjects in this research were PAI teachers at SMPN 1 Kapuas, while the objects in this research were the form of instilling the values of inter-religious tolerance in students at SMPN 1 Kapuas Tengah and the factors that supported or hindered them. In extracting data, researchers used interview, observation and documentation methods. Data processing is carried out using editing techniques, data classification and data interpretation. Meanwhile, the data analysis technique uses qualitative descriptive analysis by describing each data obtained and to obtain conclusions the researcher uses an inductive method regarding instilling tolerance values at the research location.Based on the research results, it is known that the form of instilling the values of tolerance between religious communities at SMPN 1 Kapuas Tengah: cultivating an attitude of mutual respect, cultivating an attitude of mutual respect and in the form of adjusting existing problems. The supporting factors are the condition of students who are accustomed to inter-religious tolerance. Because basically the teaching of tolerance is always taught to students when they are in their respective home environments, while the inhibiting factors based on an interview with one of the teachers stated that there were no significant obstacles. Keywords: Cultivation, Religious Community, Tolerance Values. Abstrak: Penelitian ini membahas tentang Penanaman Nilai-Nilai Toleransi Antar Umat Beragama Pada Siswa SMPN 1 Kapuas Tengah. Rumusan masalah dalam penelitian ini adalah Penanaman Nilai-Nilai Toleransi Beragama di SMPN 1 Kapuas Tengah, hambatan yang dihadapi dalam menanamkan nilai-nilai toleransi beragama di SMPN 1 Kapuas Tengah. Subjek dalam penelitian ini adalah guru PAI yang ada di SMPN 1 Kapuas, sedangkan objek dalam penelitian ini adalah Bentuk penanaman nilai-nilai toleransi antar umat beragama pada siswa di SMPN 1 Kapuas Tengah dan faktor-faktor yang mendukung atau menghambat. Dalam penggalian data peneliti menggunakan metode wawancara, observasi dan dokumentasi. Pengolahan data dilakukan dengan teknik editing, klasifikasi data dan interpretasi data. Sedangkan teknik analisis data menggunakan analisis deskriftif kualitatif dengan cara menggambarkan setiap data yang diperoleh dan untuk mendapatkan kesimpulan peneliti menggunakan metode induktif tentang penanaman nilai-nilai toleransi dilokasi penelitian.Berdasarkan hasil penelitian, maka diketahui bahwa bentuk penanaman nilai-nilai toleransi antar umat beragama di SMPN 1 Kapuas tengah: penanaman sikap saling menghormati, penanaman sikap saling menghargai dan berupa penyesuaian masalah yang ada. Adapun faktor-faktor yang mendukung adalah keadaan siswa yang sudah terbiasa dengan bertoleransi antar umat beragama. Karena pada dasarnya pengajaran toleransi ini selalu diajarkan kepada para siswa ketika berada dilingkungan rumahnya masing-masing, sedangkan faktor yang menghambat berdasarkan wawancara dengan salah satu guru beliau menyatakan tidak ada yang menjadi hambatan berarti. Kata Kunci: Nilai-Nilai Toleransi, Penanaman, Umat Beragama.